176k views
5 votes
Rewrite the function by completing the square. f ( x ) = 4 x 2 + 1 2 x + 9

User Menghanl
by
5.9k points

2 Answers

3 votes

Answer:

x= 1.5

Explanation:

4x2+12x+9=0

÷4 ÷4 ÷4

Divide by 4

4(x2+3x+2.25)=0

Factor

(x+1.5)(x+1.5)

x+1.5=0

x=-1.5

User Rahul Ravi
by
6.4k points
4 votes

Answer:


4(x+(3)/(2))^2+0

To solve
ax^2+bx+c=0 by completing the square:

1. Transform the equation so that the constant term, c , is alone on the right side.

2. If a, the leading coefficient (the coefficient of the
x^2 term), is not equal to 1, divide both sides by a.

3. Add the square of half the coefficient of the x-term,
((b)/(2a))^2 to both sides of the equation.

4. Factor the left side as the square of a binomial.

5. Take the square root of both sides. (Remember:
(x+q)^2=r is equivalent to
x+q=+-√(r))

Hope this helps and have a great day!!

User Chriswoodford
by
6.2k points